Strengthening the Social Responsibility of Construction Enterprises in the Context of Sustainable Development as a Criterion and Prerequisite for Enhancing Their Competitiveness - Lopatka, S. (Global Prosperity, 2023)
This article explores the growing importance of corporate social responsibility (CSR) in the construction sector as a strategic component of sustainable development and a decisive factor for long-term competitiveness. In the face of global environmental challenges, socio-economic volatility, and post-war recovery needs – particularly relevant for transitional economies such as Ukraine – construction enterprises are increasingly viewed as key stakeholders in the creation of inclusive, safe, and ecologically resilient living environments. The study highlights the transition of CSR from a peripheral philanthropic function to an integrated system of values and practices embedded in all stages of construction activity, from design and planning to execution and stakeholder engagement. Drawing upon the principles of ESG (Environmental, Social, and Governance) management and international CSR frameworks, the paper identifies several core domains where socially responsible practices generate measurable competitive advantages. These include the implementation of energy-efficient technologies, inclusive urban design, mitigation of environmental impacts, participatory urban planning, and the institutionalization of health, safety, and labor rights. Special attention is given to the internal dimension of CSR, emphasizing workforce development, psychosocial wellbeing, and ethical corporate culture as key determinants of productivity and reputational capital. Using a multidisciplinary approach and referencing leading academic and policy sources, the article argues for a systemic integration of CSR principles into the governance and operational models of construction enterprises. This integration is presented not only as a response to rising regulatory and societal expectations but as a proactive strategy for contributing to national resilience, local community well-being, and international alignment with the Sustainable Development Goals (SDGs). The findings support the view that CSR in construction is both a moral obligation and a competitive asset, capable of transforming companies into agents of socio-spatial transformation.